A robust, general automatic phase correction algorithm for high‐resolution NMR data - Zorin, Vadim; Bernstein, Michael A.; Cobas, Carlos (Magnetic resonance in chemistry, 2017)
The trends towards rapid NMR data acquisition, automated NMR spectrum analysis, and data processing and analysis by more naïve users combine to place a higher burden on data processing software to automatically process these data. Downstream data analysis is compromised by poor processing, and the automated processing algorithms must therefore be robust and accurate. We describe a new algorithm for automatic phase correction of frequency‐domain, high‐resolution NMR spectra. We show this to be reliable for data derived from a wide variety of typical NMR usages. We therefore conclude that the method will have wide‐spread applicability and a positive impact on automated spectral processing and analysis. Copyright © 2017 John Wiley & Sons, Ltd. New automatic phase correction algorithm for high‐resolution 1D NMR data.